Factors associated with stunting in children aged under five years: A systematic review - Prasetyo, Yoyok Bekti; Syafi'i, Doni Muhammad (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2024)
Background: Nutritional intake determines the future growth and development of children under five. Objectives: This article aims to analyze the direct and indirect determinants of stunting. Methods: Systematic literature review selected from Scient Direct, Taylor & Francis, ProQuest, Wiley Online Library, and Pubmed. Publication years: Post-2017. Articles will be selected using PRISMA (Preferred. Reporting Items for Systematic. Reviews and Meta-analyses). Result: The direct factors causing stunting include boys (aOR 2.2; 95% CI 1.1-4.2) and low birth weight (aOR 2.55; 95% CI 2.05–3.15). Indirect factors include low socioeconomic (aOR = 5.41, 95% CI 3.91–7.48); low education (aOR = 2.55, 95% CI 1.26–5.17); pregnancy interval (AOR 0.71; 95% CI 0.58-0.87); and physical violence against mothers (aOR 1.83; 95% CI 1.21-2.77). Conclusions: The causes of stunting include child and other factors. Factors outside the child have more variations, including maternal, nutritional, and environmental factors.